2022
DOI: 10.26434/chemrxiv-2022-7cvbc-v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Limits of the quantum cognition hypothesis: 31P singlet order lifetimes of pyrophosphate from experiment and simulation

Abstract: A proposal of quantum cognition advances the hypothesis that quantum entanglement between 31P nuclei could serve as a means of information storage in the brain. Testing this hypothesis requires an understanding of how long-lived these quantum effects may be. We used NMR spectroscopy and molecular dynamics simulations to study the mechanisms that limit these quantum processes in 18O-enriched molecules of pyrophosphate, the simplest biomolecule that can sustain quantum-entangled 31P nuclear spin singlet states. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 22 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Additionally, the latter study suggests that singlet lifetimes may be reduced further in a more realistic biological environment, and identifies spin-rotation relaxation as the dominant relaxation pathway. 21 While our model neglects spin-rotation relaxation (due to the larger size of the Posner molecule), it will be interesting to see how our results differ after its inclusion. The singlet lifetimes reported in the above studies are of the same order as that of the Posner molecule in the current study and suggest that, without conclusive evidence of the presence of isolated Posner molecules in vivo, the longevity of the singlet state reported in this study is comparable to that found in other phosphorus compounds in vitro.…”
Section: The Journal Ofmentioning
confidence: 95%
See 3 more Smart Citations
“…Additionally, the latter study suggests that singlet lifetimes may be reduced further in a more realistic biological environment, and identifies spin-rotation relaxation as the dominant relaxation pathway. 21 While our model neglects spin-rotation relaxation (due to the larger size of the Posner molecule), it will be interesting to see how our results differ after its inclusion. The singlet lifetimes reported in the above studies are of the same order as that of the Posner molecule in the current study and suggest that, without conclusive evidence of the presence of isolated Posner molecules in vivo, the longevity of the singlet state reported in this study is comparable to that found in other phosphorus compounds in vitro.…”
Section: The Journal Ofmentioning
confidence: 95%
“…Any dipolar coupling with the solvent is expected to average out to zero in the presence of rapid, independent tumbling motion of the molecule. Finally, spin-rotation relaxation, which is thought to be the dominant relaxation mechanism for pyrophosphates, , is neglected here under the assumption that the standard deviation in the angular velocity is expected to be much smaller for the larger Posner molecule. Of all these pathways then, the intermolecular contribution is clearly negligible at reasonable concentrations, and the dominant relaxation is induced by the 15 pairwise intramolecular dipolar nuclear spin couplings, the detailed form of which can be found in the SI.…”
mentioning
confidence: 99%
See 2 more Smart Citations